The Effect of Pocket Book-Based Education on Adolescent Girls’ Knowledge of Menstrual Personal Hygiene: A Quasi-Experimental Study - Nursyahid Siregar; Elisa Goretti Sinaga; Nurul Ummul Kurnia (Napande: Jurnal Bidan, 2026)
Background: Poor menstrual hygiene remains a significant public health concern among adolescent girls. Around 60% of adolescent girls have inadequate knowledge and practices regarding menstrual hygiene, which contributes to a 30–40% risk of reproductive tract infections (RTIs). Local studies in East Kalimantan have shown that more than half (65%) of students still have only fair knowledge of menstrual personal hygiene. Therefore, effective educational media such as pocket books are needed to improve adolescents’ understanding and awareness of proper menstrual hygiene. Methods: This quasi-experimental study used a pretest–posttest control group design involving 80 seventh-grade female students at SMP Negeri 29 Samarinda. The intervention group received pocket-book education, while the control group received conventional education. Data were analyzed using the Wilcoxon and Mann–Whitney tests. Results: The findings showed a significant improvement in the knowledge scores of adolescent girls after receiving pocketbook education (p < 0.05). The mean knowledge score in the intervention group increased from 14.95 before intervention to 17.00 after (p = 0.001), while the control group increased from 14.20 to 15.58 (p = 0.011). The Mann–Whitney test indicated that the posttest knowledge score of the intervention group was significantly higher than that of the control group (p = 0.001). Conclusion: Education using pocket books was proven effective in significantly increasing adolescent girls’ knowledge of menstrual personal hygiene compared with conventional education. Pocket books can be utilized as a practical, engaging, and sustainable medium for reproductive health education among adolescents